2020
DOI: 10.1002/bdr2.1768
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and developmental basis of orofacial clefts

Abstract: During craniofacial development, defective growth and fusion of the upper lip and/or palate can cause orofacial clefts (OFCs), which are among the most common structural birth defects in humans. The developmental basis of OFCs includes morphogenesis of the upper lip, primary palate, secondary palate, and other orofacial structures, each consisting of diverse cell types originating from all three germ layers: the ectoderm, mesoderm, and endoderm. Cranial neural crest cells and orofacial epithelial cells are two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 296 publications
(399 reference statements)
1
37
0
1
Order By: Relevance
“…During mouse facial development, the morphogenesis of the LNP-and MNP-derived structures progresses from E10.5 to E12.5. However, MxP cells continue to grow until E15.5 to give rise to the secondary palate (Ji et al, 2020). This is consistent with our results that, at E11.5, LNP and MNP cells (m0, m1, and m2) were grouped into three clusters at different differential stages while most of the MxP cells (m3) are still at an early developmental stage.…”
Section: The Initiation Of the Ossification Is Coupled To Cell Cycle Progressionsupporting
confidence: 92%
See 1 more Smart Citation
“…During mouse facial development, the morphogenesis of the LNP-and MNP-derived structures progresses from E10.5 to E12.5. However, MxP cells continue to grow until E15.5 to give rise to the secondary palate (Ji et al, 2020). This is consistent with our results that, at E11.5, LNP and MNP cells (m0, m1, and m2) were grouped into three clusters at different differential stages while most of the MxP cells (m3) are still at an early developmental stage.…”
Section: The Initiation Of the Ossification Is Coupled To Cell Cycle Progressionsupporting
confidence: 92%
“…Therefore, it can label these tissues and their progeny cells with green fluorescence. Since the cranial NC cells migrate to their target region around E8.5 and the generation of the facial prominences is completed by E12.5 (Ji et al, 2020), we collected eGFP positive cells from E9.5, E10.5, E11.5, and E12.5 embryos using fluorescence-activated cell sorting (Fig. 1B, C).…”
Section: A Single-cell Graph Of Nc Developmental Process In the Murine Embryosmentioning
confidence: 99%
“…Defects in cytoskeleton dynamics are considered to be the cellular basis of NSOFC. 22 Qian et al showed that TPM1 encodes actin-binding proteins and is involved in cytoskeleton organization, and polymorphisms in this gene might contribute to the etiology of NSOFC. 23 Recent studies indicate that single nucleotide polymorphisms in KRT18, which encodes the type I intermediate filament chain keratin 18, are a genetic susceptibility locus for NSOFC.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoskeleton organization plays an important role in the development of the lip and palate. Defects in cytoskeleton dynamics are considered to be the cellular basis of NSOFC 22 . Qian et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the primary deficiency may involve the fusion process. In such cases, the facial prominences may grow in a normal manner and make contact, but something interferes with the molecular machinery that drives tissue fusion (reviewed in Ji et al, 2020 ). However, another possibility is that the nascent facial prominences are not able to contact one another or meet too late for proper fusion to take place.…”
Section: Introductionmentioning
confidence: 99%